Long-term Ingestion of High Fructose Corn Syrup Decreased Male Rats' Sexual Motivation - Zorlu, G.; Ozgen, A.; Ozbeg, G.; Tan, F.; Oz, Z. D.; Ozdede, M. R.; Serhatlioglu, I. (Wiley, 2022)
[Abstract Not Available]